Briefing: Negotiating value at the research–practice interface in the water sector - Jeffrey, Paul; McAdam, Ewan J.; Templeton, Michael R.; Savic, Dragan; Shucksmith, James; Amezaga, Jaime; Gormey-Gallagher, Aine (Thomas Telford (ICE Publishing), 2015)
Lessons from experiences of managing an engineering doctorate programme are delineated in this paper, with particular emphasis on the relationship between research and practice. The paper reports on applied, practice-oriented research at the UK's industrial doctoral centre for the water sector. A descriptive account of the negotiating value at the research–practice interface is presented based on decades of collective practice, during which the engineering doctorate model has matured and grown. Conclusions focus on recommendations pertaining to project management, knowledge transfer and the effective and consistent translation of academic and practitioner project details.
Keywords: Education and training; Environment; Project management